Toward a Functional Cure for Hepatitis B: The Rationale and Challenges for Therapeutic Targeting of the B Cell Immune Response - Ma, Zhiyong; Zhang, Ejuan; Gao, Shicheng; Xiong, Yong; Lu, Mengji (Frontiers in Immunology, 2019)
The central role of the cellular immune response in the control and clearance of the hepatitis B virus (HBV) infection has been well established. The contribution of humoral immunity, including B cell and antibody responses against HBV, has been investigated for a long time but has attracted increasing attention again in recent years. The anti-HBs antibody was first recognized as a marker of protective immunity after the acute resolution of the HBV infection (or vaccination) and is now defined as a biomarker for the functional cure of chronic hepatitis B (CHB). In this way, therapies targeting HBV-specific B cells and the induction of an anti-HBs antibody response are essential elements of a rational strategy to terminate chronic HBV infection. However, a high load of HBsAg in the blood, which has been proposed to induce antigen-specific immune tolerance, represents a major obstacle to curing CHB. Long-term antiviral treatment by nucleoside analogs, by targeting viral translation by siRNA, by inhibiting HBsAg release via nucleic acid polymers, or by neutralizing HBsAg via specific antibodies could potentially reduce the HBsAg load in CHB patients. A combined strategy including a reduction of the HBsAg load via the above treatments and the therapeutic targeting of B cells by vaccination may induce the appearance of anti-HBs antibodies and lead to a functional cure of CHB.